2021
DOI: 10.3389/fphys.2021.792633
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Context of Obstructive Sleep Apnea and Metabolic Diseases

Abstract: The relationship between obstructive sleep apnea (OSA) and endocrine and metabolic disease is unequivocal. OSA, which is characterized by intermittent hypoxia and sleep fragmentation, leads to and exacerbates obesity, metabolic syndrome, and type 2 diabetes (T2D) as well as endocrine disturbances, such as hypothyroidism and Cushing syndrome, among others. However, this relationship is bidirectional with endocrine and metabolic diseases being considered major risk factors for the development of OSA. For example… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 180 publications
(228 reference statements)
1
23
0
Order By: Relevance
“…Met-S multiplies the risk of type 2 diabetes by five [ 2 , 3 ] and that of other cardiovascular diseases by three [ 2 , 4 ]. Similarly, people with Met-S also have a greater predisposition for polycystic ovaries in women [ 5 ]; nonalcoholic fatty liver, especially in men [ 6 ]; asthmatic symptoms [ 7 ]; sleep problems [ 8 ]; certain oncological processes [ 9 , 10 ]; and, in recent years, its relationship with sarcopenia has been evidenced [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Met-S multiplies the risk of type 2 diabetes by five [ 2 , 3 ] and that of other cardiovascular diseases by three [ 2 , 4 ]. Similarly, people with Met-S also have a greater predisposition for polycystic ovaries in women [ 5 ]; nonalcoholic fatty liver, especially in men [ 6 ]; asthmatic symptoms [ 7 ]; sleep problems [ 8 ]; certain oncological processes [ 9 , 10 ]; and, in recent years, its relationship with sarcopenia has been evidenced [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given the sex-based differences in the context of OSA and metabolic diseases [25], the association between OSA, IR, and MetS was evaluated separately by sex. Categorical variables were compared using chi-square or Fisher's exact tests and presented as weighted percentages with standard error (SE).…”
Section: Discussionmentioning
confidence: 99%
“…Another noteworthy finding from our study is that OSA did not affect female infertility. OSA is a severe public health disease affecting 3–7% of men and 2–5% of women [ 35 ], and there are significant gender differences in the pathological mechanism, symptoms presentation, and disease manifestation in the link between OSA and dys-metabolism [ 36 ]. Gender differences regarding OSA might possibly explain why OSA affects male infertility instead of female infertility in consequence.…”
Section: Discussionmentioning
confidence: 99%
“…The study indicated that, in women with infertility, only 1.38% had a history of OSA compared with 0.63% of fertile controls. The low incidence rate of OSA compared with the general female population [ 36 ] may be explained by the fact that OSA is more common in older women than in younger. Nevertheless, the limitation in the number of participants might possibly conclude that further study is needed to better clarify the association of OSA with female infertility.…”
Section: Discussionmentioning
confidence: 99%